2021
DOI: 10.3389/fmars.2021.679844
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Scale Ocean Currents Derived From in situ Observations in Anticipation of the Upcoming SWOT Altimetric Mission

Abstract: After the launch of the Surface Water and Ocean Topography (SWOT) satellite planned for 2022, the region around the Balearic Islands (western Mediterranean Sea) will be the target of several in situ sampling campaigns aimed at validating the first available tranche of SWOT data. In preparation for this validation, the PRE-SWOT cruise in 2018 was conceived to explore the three-dimensional (3D) circulation at scales of 20 km that SWOT aims to resolve, included in the fine-scale range (1–100 km) as defined by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 88 publications
0
26
0
Order By: Relevance
“…This prediction can work on short-term studies (2-3 days) and can support management and prediction tools for oil spills and other floating contaminants. Our approach will undoubtedly benefit from future satellite altimetry missions, such as SWOT [56,69,70], in terms of their observations with increased resolution and reliability close to the coast, and may be extended to other environmental applications, such as conservation [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prediction can work on short-term studies (2-3 days) and can support management and prediction tools for oil spills and other floating contaminants. Our approach will undoubtedly benefit from future satellite altimetry missions, such as SWOT [56,69,70], in terms of their observations with increased resolution and reliability close to the coast, and may be extended to other environmental applications, such as conservation [52].…”
Section: Discussionmentioning
confidence: 99%
“…In this coastal region, altimetry seemed insufficient for the detection of near-shore fronts where the spilled oil was observed (the red slicks in Figure 9c). This is not surprising, as one limitation for satellite altimeters is their inaccuracy near the land shore (at least 5-10 km from the coast) that increases in regions of small Rossby radius such as in the Mediterranean [55][56][57][58][59]. For a more reliable near-shore analysis in the southeastern Mediterranean basin, we chose the data assimilating model analysis from the Mediterranean Forecast System (MFS).…”
Section: Regional Application Of Lagrangian Fronts On the East Mediterranean Pollution: Coastal Dynamics And Strong Windmentioning
confidence: 99%
“…Aside from this, the surface circulation could be less accurate closer to the coast, where previous studies have shown a declining altimetry accuracy in the Levantine basin . Accordingly, the use of higher spatiotemporal resolution products, such as accurate models or upcoming altimetry missions like SWOT that will provide more reliability close to the coast (Morrow et al, 2019;Barceló-Llull et al, 2021), will improve the decomposition of the surface circulation by our method without changing the main conclusions.…”
Section: Vortex-dominated Cluster Analysismentioning
confidence: 99%
“…To anticipate the daily high-resolution two-dimensional (2D) SSH fields that SWOT will provide, the PRE-SWOT multi-platform experiment was conducted in the southern region of the Balearic Islands (western Mediterranean Sea) in May 2018 (Barceló-Llull et al, 2018, Barceló-Llull et al, 2021. In situ observations from gliders, drifters, a Conductivity Temperature Depth probe (CTD), and a hull-mounted Acoustic Doppler Current Profiler (ADCP), were collected to evaluate the horizontal and vertical velocities associated with the scales that SWOT will resolve (defined as fine scales).…”
Section: Introduction To T23mentioning
confidence: 99%